The Mechanisms of Chief Executive Officer Characteristics and Corporate Social Responsibility Reporting: Evidence From Chinese-Listed Firms - Zhao, Xingxin; Wang, Min; Zhan, Xinrui; Liu, Yunqing (Frontiers in Psychology, 2022)
Corporate social responsibility (CSR) strategy hinges largely on the CEO characteristics in the context of an emerging market. Based on a sample of 16,144 firm-year observations obtained from 1,370 unique Chinese-listed firms, which whether voluntarily issue CSR reports over the period 2008–2019, this paper empirically examined the impact of CEO characteristics on the likelihood of issuing CSR reports. We find that CEO age, MBA education, international experience and political ideology consciousness are positively associated with the possibility of issuing CSR reports, while a newly appointed CEO will decrease the likelihood of issuing CSR reports. Moreover, we consider a contingent factor, namely CEO power over the board, can significantly enhance the relationship between CEO age, political ideology consciousness, and the likelihood of issuing CSR reports. Furthermore, there’s no significant evidence indicating that CEO power can moderate the relationship between MBA education, international experience, and the likelihood of issuing CSR reports. Nonetheless, CEO power moderates the negative relationship between a newly appointed CEO and CSR reporting initiatives. This study attaches understandings to the extant literature that how top management characteristics can shape firm CSR strategies.